Do borrowing constraints matter for intergenerational educational mobility? Evidence from Japan - Yoko Niimi (Asian Development Bank Institute (ADBI), 2018)
This paper examines the intergenerational transmission of educational attainment using data on Japan. By exploiting unique information on whether children have ever given up schooling for financial reasons and, if they have, which level of schooling they have forgone, it attempts to assess the role of borrowing constraints in determining intergenerational educational mobility in a more direct manner than previous attempts made in the literature. We find that there has been a steady increase in the extent of the intergenerational transmission of educational attainment, resulting in lower intergenerational mobility, during the postwar period in Japan. We also find that while the importance of borrowing constraints for determining intergenerational educational mobility declined at one time, it seems to have become significant enough once again to lower intergenerational educational mobility for the youngest cohort we examined in this paper. However, our analysis also shows that the relative importance of adolescent academic ability for children's educational attainment has increased in recent years, thereby underlining the increasing importance of early investments in children's human capital for their subsequent academic advancement.
Keywords: I24; J62; 330; borrowing constraints; education; intergenerational mobility; Japan